2017
DOI: 10.3390/w9100754
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations in Environmental Variables in Relation to Phytoplankton Community Structure in a Eutrophic River-Type Reservoir

Abstract: This study assesses spatial and temporal variation in environmental variables in relation to phytoplankton community size and composition in a typically eutrophic river reservoir (Hai River, northern China). The aim is to identify environmental parameters governing spatial and temporal differences in phytoplankton density and composition. Physicochemical parameters, including nutrient concentrations, were determined in monthly surface water samples from 2015. The average concentration of key eutrophication ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
2
4
0
1
Order By: Relevance
“…These loadings indicated that the main variation in algal density is related to the parameters pH and TA at the station KE. Similar results also are observed by Zhao et al (2017) from a Hai River reservoir, Tianjin City. In our study, it was seen that spatial variation in algal groups accurately reflects the water conditions of the wetland.…”
Section: Phytoplankton Abundance Composition and Distributionsupporting
confidence: 86%
“…These loadings indicated that the main variation in algal density is related to the parameters pH and TA at the station KE. Similar results also are observed by Zhao et al (2017) from a Hai River reservoir, Tianjin City. In our study, it was seen that spatial variation in algal groups accurately reflects the water conditions of the wetland.…”
Section: Phytoplankton Abundance Composition and Distributionsupporting
confidence: 86%
“…This may be correlated with a continuous supply of nutrients that is a eutrophic condition that induces rapid growth of some groups or species of microalgae, especially Cyanophyta. Zhao et al (2017) also reported lower J' (0.39-0.45) in an environment that had a higher abundance of Cyanophyta due to eutrophic conditions, similar to that found in shrimp ponds.…”
Section: Phytoplankton Communitysupporting
confidence: 69%
“…Even if this auto-correlation was not considered, it could be seen that some models using NO 3 -N or TN as input features along with air temperature were also very accurate. From these results, we could assume that nitrogen compounds were directly or indirectly involved in cyanobacterial blooms [23,51]. Therefore, further research could identify if the control of nitrogen compounds flowing into rivers or reservoirs according to the air temperature is possible to make the cyanobacterial blooms produce or fade.…”
Section: Discussionmentioning
confidence: 99%